Nationwide survey of severe postpartum hemorrhage in Japan: an exploratory study using the national database of health insurance claims. (2nd November 2019) - Sato, Mai; Kondoh, Eiji; Iwao, Tomohide; Hiragi, Shusuke; Okamoto, Kazuya; Tamura, Hiroshi; Mogami, Haruta; Chigusa, Yoshitsugu; Kuroda, Tomohiro; Mandai, Masaki; Konishi, Ikuo; Kato, Genta
Abstract: Aim: The aim of this study was to investigate epidemiological and clinical aspects of severe postpartum hemorrhage (PPH) in Japan. Methods: We used national health insurance claims from 2011 to 2014 provided by the Ministry of Health, Labour and Welfare. The data included randomly selected claims that covered 10% of all inpatients in October, a so-called sampling dataset (covering 1/120 inpatients per year). We extracted claims for transfused blood, and further narrowed down the claims by names of diseases linked to PPH. As most referral obstetric facilities have adopted the diagnosis procedure combination (DPC)-based payment system while small-scale obstetric facilities have not (non-DPC facilities), the claims were also analyzed separately for DPC and non-DPC facilities. We assessed the incidence and causes of PPH, transfusion volume of red blood cells (RBC) and fresh frozen plasma (FFP), and surgical hemostatic management. Results: The number of PPH cases that required blood transfusion in the sampling dataset was 29, 29, 32, and 36 in 2011, 2012, 2013, and 2014, respectively. The leading cause of PPH was uterine atony followed by placental abruption. Although no specific trends were observed for the volume of transfused RBC (1467 ± 234 ml in 2014), there was a steady increase in the rate of FFP utilization in non-DPC facilities from 37% to 79% over the 4-year sampling period. Intrauterine balloon tamponade emerged in 2014. Conclusion: This nationwide survey indicates that the annual incidence of severe PPH is increasing. Furthermore, FFP has become more prevalent in small-scale obstetric facilities.